Wide angle digital holographic interferometry with real-time optical reconstruction - Kujawinska, Malgorzata; Finke, Grzegorz; Garbat, Piotr; Faldorf, Claas; Hennelly, Bryan M. (Photonics Letters of Poland, 2012)
In the paper we will discuss the wide angle capture and display systems applied for digital holographic interferometry (DHI). The static capture system is based on a single camera and an object located at a rotational stage. The holograms are captured sequentially in time during object loading and the phases at a hologram plane are calculated by phase shifting method. The dynamic capture system employs several cameras located around an object and simultaneous capture of several holograms is performed with the frequency of impulse laser applied. For both DHI capture systems the holographic display configuration is proposed. Multiple spatial light modulators aligned in circular configuration are put to work together. In the paper the main requirements for optical reconstruction of resultant interferograms originated from both capture systems are discussed. The results of experiments are presented and analysed. Full Text: PDF References T. Kreis, “ Handbook of holographi interferometry: Optical and digital methods”, Wiley-VCH Verlag GmbH, 2005. A. Michałkiewicz, Kujawińska M., Stasiewicz K., "Digital holographic cameras and data processing for remote monitoring and measurements of mechanical parts", Optoelectronics Review, v. 16, 68-75, 2008CrossRef T. Kozacki, M. Kujawinska, G. Finke, B. Hennely, N. Pandey, "Extended viewing angle holographic display system with tilted SLMs in a circular configuration", Appl. Opt., 52, 1771-1780, 2012.CrossRef M. Kujawinska, T. Kozacki, Holographic Television: Status and Future, in Optical Imaging and Metrology: Selected Topics, 55-93, (eds W. Osten and N. Reingand), Wiley-VCH Verlag GmbH. Kelly D.P. et al., "Digital Holographic Capture and Optoelectronic Reconstruction for 3D Displays", Int. J. Digital Multimedia Broadcasting, 2010, Article ID 759323, 2010. CrossRef